PERAN OMBUDSMAN DALAM MENJAGA GOOD GOVERNANCE DI INDONESIA: ANALISIS DARI PERSPEKTIF HUKUM TATA NEGARA - ARMA NURLAILIY, NYI AYU; Nuriskandar, Lalu Hendri (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2024)
This research aims to analyse the role of the Ombudsman in maintaining good governance in Indonesia from the perspective of Constitutional Law. As an independent state institution, the Ombudsman has the main function of supervising public services carried out by government institutions and state-owned enterprises (BUMN), with the aim of ensuring that public administration runs in accordance with the principles of good governance, such as transparency, accountability and participation. public. This research explores the extent of the authority and effectiveness of the Ombudsman in carrying out its supervisory duties, as well as the challenges faced in ensuring the implementation of the recommendations issued. The approach used in this research is juridical-normative, with data analysis sourced from statutory regulations, decisions and relevant literature. The research results show that although the Ombudsman has contributed significantly in encouraging good governance practices, there are a number of obstacles, such as limited legal authority and resources, which affect the effectiveness of its supervision. In addition, the level of compliance of supervised institutions with the Ombudsman's recommendations still requires improvement. This research suggests strengthening the authority of the Ombudsman through revision of statutory regulations, increasing resources, and closer collaboration with other institutions, both at the national and international levels, to strengthen the role of the Ombudsman in maintaining good governance in Indonesia.